EFFECTIVENESS OF PROJECT-BASED LEARNING MODELS TO IMPROVE INDEPENDENCE AND COLLABORATION IN CHILDREN AGED 4-5 YEARS - Sulastya; Sodik, Nurul Aini MM; Sumirat, Elva S; Umar, Sri Yulan; Putri, Fiola Indah; Mannaasai, Annisa Fahmi (PG PAUD Universitas Negeri Surabaya, 2024)
The project-based learning approach allows children to be actively involved in activities encouraging them to take independent roles and work together to complete tasks. This study used a quantitative experimental method with a single-group pretest-posttest design involving 30 children. The sample in the survey was group A children aged 4-5 years at Agropolitan Kindergarten, Kabila District, Kabila Bone Regency, Gorontalo, totaling 15 children. The study results showed that Before treatment (pretest), the average scores of independence and collaboration were at a lower level, namely 52 and 48 respectively. After being given treatment in the form of Project-Based Learning (posttest), the independence score increased to 78, while the collaboration score increased to 75. From the results of the statistical analysis of the t-test hypothesis test above, the researcher can conclude that the significant test obtained a t-count value = 14.38 independence and 14.68 collaboration while the t-table value at (α) = 0.05 is as large as 0.242. If t-count> t-table; 14.38> 0.242 and 14.68> 0.242 then H0 is rejected and H1 is accepted. By being accepted, the hypothesis is accepted, meaning that there is an Influence of the Project-Based Learning Model to Improve Independence and Collaboration in Children Aged 4-5 Years at TK Pembina Agropolitan Kabila Bone Gorontalo. This study enriches the literature on project-based learning in early childhood education and implies that this approach effectively builds the foundation of independence and collaboration. Further studies can explore the long-term impact of this model on other aspects such as children's creativity and problem solving. situs slot gacor Key Words: Project Based Learning (PBL) Model; Independence, Collaboration